Survival Rate of Patients with Glioblastoma Treated with Radiotherapy and Temozolomide Compared to Radiotherapy Alone: A Comprehensive Systematic Review and Meta-Analysis - Billy Billy; Andreas Christoper; Indri Meiya Sembiring; Donny Donny; Marsal Risfandi (AKSONA, 2026)
Highlight: Glioblastoma is the most prevalent and deadly primary malignant brain tumor. The prognosis for glioblastoma remains unfavorable because of detrimental prognostic factors. Appropriate and advanced treatment can help in improving the survival rate of patients with glioblastoma.   ABSTRACT Introduction: Glioblastoma is one of the deadly malignant brain tumor associated with a highly unfavorable prognosis, making it one of the significant challenge for clinicas due to its unfavorable poor prognostic. Patients with glioblastomas may experience headaches, nausea, vomiting, loss of consciousness, seizure/convulsion, altered mental status, and focal neurological deficits. Chemotherapy, radiation, and surgical resection became standar therapeutic options for patient with glioblastoma. This advanced treatment is important for increasing the survival rate of patients. Objective: This study aimed to evaluate survival outcomes in patients with glioblastoma treated with temozolomide plus radiotherapy compared with radiotherapy alone Methods: This study followed PRISMA guidelines and applied the PICO framework. Included studies (randomized controlled trials (RCTs), quasi-experimental, observational, and case-control) evaluated survival outcomes in glioblastoma patients treated with radiotherapy plus 6 cycles of adjuvant temozolomide versus radiotherapy alone. Studies not relevant to this treatment comparison were excluded. Results: Following three stages of screening, six articles relevant to the systematic review were selected for full-text analysis. Overall, radiotherapy plus temozolomide had better outcomes than radiotherapy alone. Median overall survival (OS) ranged from 10 to 17.5 months in patients with radiotherapy plus temozolomide, compared with 8 to 14 months in those treated with radiotherapy alone. Median progression-free survival (PFS) ranged from 6 to 10.1 months in the combined-treatment group, and 3.8 treated with radiotherapy alone. Conclusion: Continuous daily TMZ and concurrent RT followed by adjuvan TMZ is safe and can increase survival. Our findings support the positive impact of the RT + TMZ relatonship on long-term (> 2 years) follow up.